The Work of Architect Franja Urban in the area of Pomoravlje and Šumadija - Putnik Prica, Vladana (Arhitektura i urbanizam, 2025)
Franja Urban is one of the foreign architects who, after the First World War, decided to immigrate to the Kingdom of Serbs, Croats and Slovenes, thus achieving a very productive career. Although most of his buildings were completed in Belgrade, Urban managed to work in other cities and towns, thanks to his good relationship with investors. So far, it is known that Urban worked in Loznica, Jagodina, Ćuprija and Aranđelovac. Jagodina is the second city after Belgrade in terms of the number of Urban’s buildings, and the only city where one of them is listed as a historic landmark. Despite partially salvaged project documentation for some of Urban’s buildings in Jagodina, so far, they have not been the subject of a more detailed monographic study, and until recently, the houses he designed in Ćuprija and Aranđelovac were not known to domestic historiography. Therefore, this article presents a continuation of research into the life and work of architect Franja Urban, in order to more completely analyse this underresearched and little-known part of his opus.
Keywords: Franja Urban; Jagodina; Aranđelovac; Ćuprija